Understanding the engagement and consequences of user generated online video and its virality towards generation Y political inclination / Wan Hartini Wan Zainodin - Wan Zainodin, Wan Hartini (Institute of Graduate Studies, UiTM, 2018)
This qualitative study focuses the engagement and consequences of user generated online video and its virality towards Gen Y political inclination. To gain insights on the central focus of this study, six research questions were addressed : (1) Why Gen Y are utilizing the User-generated online video in understanding the state political scenario?, (2) How does virality of User-generated online video contributes to voting decision among Gen Y?, 3) How does the User-generated online video and its virality contribute to the perception of Gen Y towards the Federal Government ruling parties?, (4) How does User-generated online video and its virality contribute to the perception of Gen Y towards the opposition parties?, (5) How does User-generated online video and its virality contribute to the perception of Gen Y towards the Federal Government ruling politicians?, and (6) How does User-generated online video and its virality contribute to the perception of Gen Y towards opposition politicians? This study was guided with three theories; (i) Uses and Gratifications Theory, (ii) Media System Independency Theory and Standpoint Theory. Using phenomenology approach, salient discoveries were obtained through indepth interviews with 15 User Generated Online Video (UGOV) User residing in Klang Valley. Data analysis was conducted simultaneously with data collection and the NVivo 11.0 software was used in the process of coding…